Epidemiological status of suicide in the Middle East and North Africa countries (MENA) from 1990 to 2017 - Saeed Amini; Parnia Bagheri; Mehdi Moradinazar; Mona Basiri; Mostafa Alimehr; Yousef Ramazani (Elsevier, 2021)
Background: Suicide is proposed as an important and growing issue in public health. The aim of this study is to compare suicide load in the Middle East and North Africa (MENA) countries in order to pave the way for correct health policy making. Methods: The population included 21 MENA countries. The data of Global Burden of Diseases in 2017 that estimate death rate for 264 causes was used. The GBD considers suicide according to definition of the ninth and tenth editions of the international classification of diseases as death due to poisoning or intentional self-injury. All suicide-related analyzes were evaluated using these indicators in excel 2016. Results: The highest percentage of total suicide DALY attributable to risk factors of Alcohol and drug use are related to United Arab Emirates and Afghanistan countries, respectively. Iran is the sole country without suicide DALY attributable to alcohol consumption risk factor. Moroccan women and Libya, Afghanistan and Yemen men have the highest DALY rates in terms of ASR in the region, respectively. Suicide incidence have an increasing trend until the age group of 20-24 and then a decreasing trend. This trend is on the rise again since the age of 65. Discussion: The necessity to improve social, cultural and economic factors along with effective measures on suicide prevention especially among low and middle income countries, performing more studies and precise registration of the cases especially in the areas that suicide is considered social stigma and crime should be considered as high agenda in national and regional strategies.